2020
DOI: 10.1037/dev0000991
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive adolescent benefits in positive school transitions: Evidence for vantage sensitivity in Japanese high-schoolers.

Abstract: Some researchers indicate that the transition to high school deflects adolescent developmental trajectories. Others assert that it provides a new possibility for the promotion of adolescents' socioemotional well-being. One critical view missing in such claims is that individual variabilities interact with environmental influences. We employed the framework of Differential Susceptibility Theory, which postulates that individual susceptibilities moderate external influences for better and for worse. To clarify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 85 publications
(177 reference statements)
5
33
0
Order By: Relevance
“…As the literature on DST suggests, susceptible individuals are more responsive to both positive and negative external information [ 38 , 39 , 42 ]; thus, this moderation effect can function as a “hidden efficacy” of the interventions [ 59 ]. Importantly, few empirical studies have been conducted in non-western contexts [ 39 , 43 ]; nonetheless, these results replicated previous findings on the moderation effects of SPS on intervention efficacy reported from different cultural backgrounds [ 36 , 37 ]. This suggests that phenotypic SPS—underpinned by biophysiological substrates [ 32 , 34 , 35 ]—predicts the strength of individual responsiveness to the external information irrespective of the societal differences.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As the literature on DST suggests, susceptible individuals are more responsive to both positive and negative external information [ 38 , 39 , 42 ]; thus, this moderation effect can function as a “hidden efficacy” of the interventions [ 59 ]. Importantly, few empirical studies have been conducted in non-western contexts [ 39 , 43 ]; nonetheless, these results replicated previous findings on the moderation effects of SPS on intervention efficacy reported from different cultural backgrounds [ 36 , 37 ]. This suggests that phenotypic SPS—underpinned by biophysiological substrates [ 32 , 34 , 35 ]—predicts the strength of individual responsiveness to the external information irrespective of the societal differences.…”
Section: Discussionsupporting
confidence: 83%
“…Then, to investigate the moderation effects of gender and individual sensitivity from a DST perspective, we hypothesized that highly sensitive youths, particularly girls, would report lower well-being and higher depression at baseline but would show greater positive outcomes than less sensitive students after intervention. Since few empirical studies on this subject have been reported in Japan, or more broadly, non-Western countries [ 43 ], this empirical study will provide a valuable contribution to adolescent intervention studies in different cultural contexts and will further our understanding of person x environmental interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Given this theory, it is possible that positive emotions were induced by the positive video because highly sensitive people are more likely to process information more deeply and have heightened emotional reactivity to environmental stimuli. Conversely, as reported in several studies and in our results, individuals with low sensitivity are less likely to benefit from positive interventions HIGHLY SENSITIVE PERSON (e.g., Nocentini et al, 2018) and supportive environment (e.g., Iimura & Kibe, 2020). In summary, Study 4 supported the validity of the newly developed HSP-J10.…”
Section: Discussionsupporting
confidence: 84%
“…More recently, it has been confirmed that Environmental Sensitivity also moderates the positive effects of a supportive environment (e.g., Iimura & Kibe, 2020;Kibe et al, 2020;Nocentini et al, 2018;Pluess & Boniwell, 2015). For example, highly sensitive children are more likely to benefit (e.g., lower depression and anxiety) from school-based positive psychological interventions (e.g., resilience training and bullying prevention interventions), which is called Vantage Sensitivity.…”
Section: Highly Sensitive Personmentioning
confidence: 98%
“…Although the Japanese government is currently promoting the 6‐6 system, which does not require major changes in the school environment and high school entrance examinations, to prevent students’ maladjustment (Ministry of Education, Culture, Sports, Science & Technology in Japan, 2013), it may not be an evidence‐based policy based on the findings of this study. Other covariates (e.g., improving the quality of the high school environment; Iimura & Kibe, 2020) may need to be investigated in future studies to consider desirable interventions and educational policies that support students’ socio‐emotional well‐being.…”
Section: Discussionmentioning
confidence: 99%